2016
DOI: 10.4067/s0301-732x2016000300007
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of ovarian follicular cysts and their effect on reproductive performance in dairy cows: A case study in Mexico

Abstract: Incidence of ovarian follicular cysts and their effect on reproductive performance in dairy cows: A case study in MexicoIncidencia de quistes foliculares ováricos y su efecto en la eficiencia reproductiva en vacas lecheras: un estudio de caso en México JL Pesántez a , O Ortiz a , J Hernández-Cerón a* ABSTRACT. The incidence of ovarian follicular cysts (OFC) in relation to reproductive performance in a dairy herd was determined. A total of 1,249 reproductive records of cows during their previous lactation cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
2
1
1
Order By: Relevance
“…Whole the experiments the percentage differences of OFC among the groups were non-significant (P>0.05). JL Pesánteza et al, 2016 observed that the incidence rate of follicular Cyst 23% in Swedish dairy farm, which slightly more than our findings (11.11±5.11) of group -A, but smaller than Group-D (70.59±11.39). Our observed values, consistent with other observations in comparatively better conditions (Melendez et al, 2003, Vanholder et al ., 2006, contrasts with the findings (1 to 16%) recorded in the 1980s, Garverick 1982, Bartlett et al, 1986) which were more similar.…”
Section: Metratis (%)contrasting
confidence: 72%
See 1 more Smart Citation
“…Whole the experiments the percentage differences of OFC among the groups were non-significant (P>0.05). JL Pesánteza et al, 2016 observed that the incidence rate of follicular Cyst 23% in Swedish dairy farm, which slightly more than our findings (11.11±5.11) of group -A, but smaller than Group-D (70.59±11.39). Our observed values, consistent with other observations in comparatively better conditions (Melendez et al, 2003, Vanholder et al ., 2006, contrasts with the findings (1 to 16%) recorded in the 1980s, Garverick 1982, Bartlett et al, 1986) which were more similar.…”
Section: Metratis (%)contrasting
confidence: 72%
“…Uterine infection, inheritance and hormonal imbalance may lead to RB (Asaduzzaman et al, 2016).Many scientists observed others risk factors of RB like age, parity, BCS, milk yield(Asaduzzaman 2016, Islam et al ., 2012), physiological status ,milk yield, feed ( Nath et al, 2014). Pesánteza et al (2016) reported that ovarian follicular cysts (OFC) in dairy cattle cause economic losses as a result of extension of the open period, cost of treatment, and risk of elimination of cows from the herd. OFC incidence risen with increasing milk production and in these conditions, between 15 to 30% of cows develop this ovarian condition within 60 days postpartum (Peter, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were also reported by Kodagali and Kerur (1968). Furthermore, higher and lower prevalence were reported in many previous studies (Tomar et al, 2002;Mittal et al, 2010;Azawi and Ali, 2011;Amin, 2016;Pesantez et al, 2016). The difference in the incidence might be due to variation in the breed, region, management practices and provision of health cover etc.…”
Section: Resultsmentioning
confidence: 82%
“…A incidência de cistos ovarianos em rebanhos de leite varia entre estudos, de 6% a 19% (Garverick, 1997) até 23% (Pesántez;Ortiz;Hernández-Cerón, 2016).…”
Section: Cistos Ovarianosunclassified